2022
DOI: 10.1158/0008-5472.can-21-1259
|View full text |Cite
|
Sign up to set email alerts
|

CircRPN2 Inhibits Aerobic Glycolysis and Metastasis in Hepatocellular Carcinoma

Abstract: Although circular RNAs (circRNA) are known to modulate tumor initiation and progression, their role in hepatocellular carcinoma (HCC) metastasis remains poorly understood. Here, three metastasis-associated circRNAs identified in a previous circRNA-sequencing study were screened and validated in two HCC cohorts. CircRPN2 was downregulated in highly metastatic HCC cell lines and HCC tissues with metastasis. Patients with HCC with lower circRPN2 levels displayed shorter overall survival and higher rates of cumula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…In GBM, circHEATR5B was expressed at low levels and could suppress glycolysis, whereas HEATR5B mRNA levels showed no significant differences and could not be regulated by ZCRB1, indicating that it is circHEATR5B but not HEATR5B mRNA that exerts glycolytic inhibition in GBM cells under the regulation of ZCRB1. Similarly, circRPN2 inhibits aerobic glycolysis in hepatocellular carcinoma and represents a therapeutic target in hepatocellular carcinoma [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In GBM, circHEATR5B was expressed at low levels and could suppress glycolysis, whereas HEATR5B mRNA levels showed no significant differences and could not be regulated by ZCRB1, indicating that it is circHEATR5B but not HEATR5B mRNA that exerts glycolytic inhibition in GBM cells under the regulation of ZCRB1. Similarly, circRPN2 inhibits aerobic glycolysis in hepatocellular carcinoma and represents a therapeutic target in hepatocellular carcinoma [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH and U6 were used as internal references. The relative mRNA levels were calculated using the 2 −ΔΔCT method [ 25 ]. Primer sequences were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…49,50,53,54 It was found that circCDR1as, circSMARCA5, circ-ZEB1.33, circSETD3, circMTO1, circSMAD2, circFBLIM1 and circHIPK3 played oncogenic or suppressive roles in the progression of HCC. 22,[55][56][57][58][59][60][61] Furthermore, a series of cir-cRNAs were found to be closely related to metabolic reprogramming in HCC, 62 such as circMAT2B, circSPECC1, circC3P1 and circRPN2 [63][64][65][66] (Table S2).…”
Section: Ncrnas and Metabolic Reprogramming In Hccmentioning
confidence: 99%
“…64 A recently published study demonstrated that circRPN2 inhibited HCC aerobic glycolysis and metastasis via accelerating enolase 1 (ENO1) degradation and modulating the miR-183-5p/FOXO1 axis. 66 Not only that, Law et al 120 found that a new piRNA (piR-Hep1) was upregulated in HCC in a small RNA transcriptome sequencing analysis. Further studies indicated that silencing piR-Hep1 could decrease AKT phosphorylation and inhibit the growth and aggressiveness of HCC.…”
Section: Okazaki Et Al Identified a New Class Of Ncrnas 20 Years Ago ...mentioning
confidence: 99%
See 1 more Smart Citation